Production software that works : a guide to concurrent development of realtime manufacturing systems - Behuniak, John A. (Digital Press, 1992)
This useful reference addresses the key tasks that are integral to realtime software development in manufacturing plants: managing the design of the system, setting up and coordinating a development organization, and implementing tools for successful.